1999
DOI: 10.1086/315051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Small Bowel Bacterial Overgrowth on the Immunogenicity of Single‐Dose Live Oral Cholera Vaccine CVD 103‐HgR

Abstract: Several live oral vaccines (polio, bovine rotavirus, CVD 103-HgR cholera) are less immunogenic in developing than in industrialized countries. It was hypothesized that proximal small bowel bacterial overgrowth (common in children in less developed countries but rare in industrialized settings) diminishes the vibriocidal antibody response to CVD 103-HgR. In total, 202 fasting Santiago schoolchildren aged 5-9 years had lactulose breath H2 tests to detect proximal small bowel bacteria 1 day before ingesting CVD 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 17 publications
0
80
0
3
Order By: Relevance
“…This finding may be of particular relevance in developing countries, where the efficacy of oral vaccines against polio, rotavirus, and cholera have showed a lower immunogenicity relative to efficacy in developed countries (75)(76)(77)(78). In a study testing a live cholera oral vaccine, Lagos et al (79) demonstrated that excessive bacterial growth in the small intestine of children in less-developed countries might contribute to the low antibody response to the vaccine. Therefore, future systems vaccinology studies should integrate metagenomics approaches to determine the composition of microflora that correlates with a particular profile of vaccine immunity.…”
Section: Vaccines For Which There Are No Knownmentioning
confidence: 97%
“…This finding may be of particular relevance in developing countries, where the efficacy of oral vaccines against polio, rotavirus, and cholera have showed a lower immunogenicity relative to efficacy in developed countries (75)(76)(77)(78). In a study testing a live cholera oral vaccine, Lagos et al (79) demonstrated that excessive bacterial growth in the small intestine of children in less-developed countries might contribute to the low antibody response to the vaccine. Therefore, future systems vaccinology studies should integrate metagenomics approaches to determine the composition of microflora that correlates with a particular profile of vaccine immunity.…”
Section: Vaccines For Which There Are No Knownmentioning
confidence: 97%
“…Owing to the invasive nature of intestinal biopsies, studies of EED have tended to rely on serum and fecal biomarkers, such as those indicative of small bowel bacterial overgrowth (e.g., hydrogen breath test), gut inflammation (e.g., fecal calprotectin and myeloperoxidase), microbial translocation (e.g., serum EndoCab) and mucosal permeability (e.g., lactulose/mannitol test). To date, the study of these biomarkers has failed to yield any consistent associations between EED and oral vaccine performance [28,98,[170][171][172][173], as discussed in detail elsewhere [Church et al, In Preparation].…”
Section: Environmental Enteric Dysfunctionmentioning
confidence: 99%
“…[65], [98], [108], [135], [171], [196] [67], [133][134][135], [198][199][200][201] [8], [181], [182], [201], [203], [204] [28], [92], [93], [128], [131], [137], [138], [140], [130], [131], [157], [202] [ [43][44][45], [49], [61][62][63][64][65][66][67][68][69][70], [197] [ [155][156][157] [28], [98], [170][171][172]…”
Section: Conclusion and Future Perspectiveunclassified
“…A recent e¤cacy study in Indonesia generated disappointing protection against cholera. This may, in part, be due to the di¡erent intestinal environment in many individuals in developing compared to developed countries (Lagos et al 1999). The normal £ora and even gut architecture can di¡er enormously between the two groups, and higher doses of CVD103 vaccine were required in locals from the tropics (Thailand) to elicit similar levels of immunity to Westerner (in this case from the USA) (Tacket et al 1992(Tacket et al , 1999Su-Arehawaratana et al 1992).…”
Section: The Immunogenicity Of Live Mucosal Vaccinesmentioning
confidence: 99%